Turkey - Investment Climate Assessment : From Crisis to Private Sector Led Growth - World Bank (World Bank, 2012)
This investment climate assessment draws on the analysis of firm-level survey data collected during April 2008-January 2009, supplemented by other sources, to provide a comprehensive and up-to-date description of the investment climate facing Turkish firms of all size classes, including the impact of government regulations and recent reforms. An important feature of the analysis is extensive use of data from comparable countries to benchmark Turkey's performance. Beyond description, the report seeks to identify key priority areas where further policy reform and institutional development could help strengthen Turkish firms' performance in such areas as productivity, export competitiveness and employment creation. A special aspect of the report is its focus on Turkey's small and medium scale enterprise (SME) sector.